2012
DOI: 10.1371/journal.pone.0045196
|View full text |Cite
|
Sign up to set email alerts
|

Study of Natural Health Product Adverse Reactions (SONAR): Active Surveillance of Adverse Events Following Concurrent Natural Health Product and Prescription Drug Use in Community Pharmacies

Abstract: BackgroundMany consumers use natural health products (NHPs) concurrently with prescription medications. As NHP-related harms are under-reported through passive surveillance, the safety of concurrent NHP-drug use remains unknown. To conduct active surveillance in participating community pharmacies to identify adverse events related to concurrent NHP-prescription drug use.Methodology/Principal FindingsParticipating pharmacists asked individuals collecting prescription medications about (i) concurrent NHP/drug us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 52 publications
1
46
0
Order By: Relevance
“…By improving the rates of AE identification and reporting, possible harms can be detected sooner, and even prevented. Our study screening questions are brief, taking approximately 15 seconds per patient to administer 19. Health professional prompting will increase the discussion around NHPs with their patients as well as improve awareness of the therapies their patients are engaged in so as to improve safety and health outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By improving the rates of AE identification and reporting, possible harms can be detected sooner, and even prevented. Our study screening questions are brief, taking approximately 15 seconds per patient to administer 19. Health professional prompting will increase the discussion around NHPs with their patients as well as improve awareness of the therapies their patients are engaged in so as to improve safety and health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, NHPs are considered by users to be safe since they are ‘natural’13; however, studies demonstrate some serious toxicities and many possible adverse reactions (ARs) with the use of these products 3 11–15. Further, NHP use is higher among patients with chronic medical conditions,16 17 where prescription drug use is likely: 58% of cardiovascular patients taking narrow therapeutic index drugs used NHPs and prescription drugs concurrently,18 compared with 39.7% of community pharmacy patients screened in Ontario (ON) 19. In patients over 50 years old, 87.4% of those taking NHPs did so in combination with drugs 20.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed methods have been presented previously (9,10) In brief, adverse events were identified in a community pharmacy where participating pharmacists and pharmacy staff were systematically asking patients collecting prescriptions for conventional medicines whether they had recently been taking NHPs such as herbal medicines, vitamins, minerals or other supplements together with prescription medications and whether they had experienced an unwanted or unexpected effect. Where adverse events were identified, the study team then obtained informed written consent from the patient prior to an in-depth guided telephone interview.…”
Section: Active Surveillancementioning
confidence: 99%
“…A formidable challenge for pharmacovigilance of NHPs is the under-reporting of suspected adverse drug reactions associated with these products (7,8). The Pharmacy Study Of Natural health product Adverse Reactions (SONAR) is a multi-centre study assessing the feasibility of a community pharmacy-based active surveillance system to identify adverse reactions related to NHPs (9,10). The study identified a patient who presented with severe sedation after intake of melatonin with two antidepressants (citalopram and nortriptyline) and one opioid analgesic (oxycodone).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the frequent use and popularity of alternative remedies, the potential benefits and risks of their use are not always clear. This uncertainty is due to several factors: use of alternative medicine is unconventional; preparations rarely meet the required standards of consistency in composition and biological activity; there is a lack of reporting of adverse events and drug interactions (6) due to a lack of professional surveillance; and specific data on organ toxicity are not readily available (7). Furthermore, many complementary health products and practices are not tested for safety or effectiveness in children, and many patients assume NHPs are safe because they are 'natural' and are unaware of any risks associated with their use.…”
mentioning
confidence: 99%